Theoretical Amino Acid-Specific Radiocarbon Content in the Environment: Hypotheses to Be Tested and Opportunities to Be Taken - Blattmann, Thomas M.; Ishikawa, Naoto F. (Frontiers in Marine Science, 2020)
Tracing of biogeochemical pathways using molecular approaches has advanced our basic understanding of the carbon cycle and life’s legacy in the sedimentary record. To this end, compound-specific radiocarbon analysis has been instrumental in shedding light on the turnover, age, and sources of a range of biomarkers embedded within complex environmental matrices. However, despite their foundational importance for life and their omnipresence throughout geologic space and time, the biogeochemical cycling of amino acids remains largely unexplored. Here, we discuss the potential of using amino acid-specific radiocarbon to deepen our knowledge of the biogeochemistry of food webs and sedimentary organic carbon.